Analysis of the Added Value of Processing Cassava into Mocaf Flour KWT Sedap Malam Bandar Lampung - Shinta Tantriadisti; Maria Ulfa; Dita Pratiwi; Tunjung Andarwangi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
The high volume of wheat imports will trigger high wheat flour production costs. Therefore, efforts must increase national wheat production and create other products to replace wheat flour. Modifying cassava flour can be an alternative substitute for wheat flour so that wheat imports can be reduced and foreign exchanges can be saved. The abundant availability of cassava as the primary raw material for mocaf flour has resulted in the development of the mocaf flour business. Processing cassava into mocaf flour aims to increase the durability of cassava, in addition to providing added value to cassava products so that the selling value of the product is higher on the market. This research analyzed the added value of processing cassava into mocaf flour at KWT Sedap Malam. The research was conducted in May - July 2023 at KWT Sedap Malam, Bandar Lampung City. This research method uses the case study method. Method Data analysis used to answer objectives related to added value uses Hayami added value calculations. This research shows that the value-added ratio processing cassava into mocaf flour at KWT Sedap Malam amounted to IDR 3,606.67 or 20.04%. The ratio of added value produced in this research is included in the ratio of medium added value.